Pengaruh Penyuluhan Kesehatan Tentang Menyusui Dengan Metode Demonstrasi Terhadap Kemampuan Ibu Menyusui Di Rumah Bersalin Wilayah Banjarsari Surakarta - Sri Lestari Dwi Astuti; Asrining Surasmi (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Health Education, Demonstration Method, Breastfeeding Ability. This study aims to know the effect of health education of the right way to breast-feed with demonstration method toward mothers ability to breast-feed in a maternity hospital, Banjarsari, Surakarta. This research is Pre-experimental with the draft of one group pre-post test design. The samples are 30 breastfeeding mothers in a maternity hospital in Banjarsari, Surakarta. The measurement conducted twice, before and after they were given counseling with demonstration method. The result of the mean of breastfeeding ability before counseling is 61,77 with standard deviation 13,423 and after counseling 95,57 with standard deviation 5,661. The development of the mean of mothers ability before and after counseling is different. It means p 0,00. There was a significant impact between a mother’s breastfeeding ability before and after counseling with the demonstration method have done.